Effect of free fatty acids contents on biodiesel quality. Pilot plant studies. (15th June 2016) - Bouaid, Abderrahim; Vázquez, Rodrigo; Martinez, Mercedes; Aracil, Jose
Highlights: Biodiesel production from a cheap raw material was studied at a pilot plant scale. The free fatty acids content of the samples influence biodiesel yield and purity. The contents of minor components as monoglycerides reduce the quality of biodiesel. Biodiesel sample with high purity was obtained using an experimental design method. Abstract: In the present work an experimental design methods have been successfully applied to produce high quality biodiesel from used frying oil (UFO) samples with different free fatty acids (FFA) contents up to 4%. The influence of the oil FFA contents on biodiesel yield and purity regarding to mono-, di- and triglycerides (MG, DG and TG) contents has been studied and optimized. Results show that the FFA content of the samples influence on biodiesel yield and purity. It has been observed that the yield of methyl ester (ME) decrease from 97.2% to 95% by increasing the FFA content of the oil from 0% to 4%. When the FFA content of the oil decrease, the DG intermediate and TG content decrease, however the MG increase in biodiesel sample, exceeding in many cases the specification of EN14214 for biodiesel standard. The optimum conditions to produce a biodiesel sample which meets the European specifications EN14214 in particular, individual glyceride contents with high purity (99%) were found to be a catalyst concentration of 0.8% and an operation temperature of 30 °C. The pilot plant process of biodiesel production using UFO as cheap raw materials has also been studied. The obtained results have been used for industrial scale up of the process.